Awareness on the Energy Saving Behaviour Among Students: Gamification Approach - Saari, Erni Marlina; Ibrahim, Norshahila; Azmi, Noor Hidayah; Isa, Nor Kalsum Mad (Universitas Negeri Padang, 2023)
Various ways or strategies to give awareness to the people of Malaysia about energy savings. However, the strategy used by researchers is the use of gamification to provide awareness for energy saving. Therefore, observations based on previous studies should be made based on gamification and energy saving. Results from previous studies show that gamification can motivate and change a person's behavior. In this study, researchers focus on obtaining information based on game design elements based on the researcher's objective which is What are the game design elements that are needed to improve learners' understanding of the content of energy-saving behavior. To qualify, researchers use quantitative methods. As a result of the study conducted, researchers present the findings of a pilot study on Bachelor of Design students. the reliability coefficients obtained for all five constructs in the assessment instrument for Bachelor of Design students. It is found that Cronbach Alpha values range from 0.955 to 0.984. This concludes the value that can be a guideline to develop gamification based on the design elements and can make users aware of energy saving.